Itaconate derivative 4-OI inhibits M1 macrophage polarization and restores its impaired function in immune thrombocytopenia through metabolic reprogramming - Qiang Liu; Anli Liu; Shaoqiu Leng; Xiaoyu Zhang; Xiaolin Wang; Zhang Cheng; Shuwen Wang; Jun Peng; Qi Feng; Sihan Zhou; Xiuyuan Hao (Chinese Medical Journal)
Abstract. Background:. Macrophage polarization anomalies and dysfunction play a crucial role in the pathogenesis of immune thrombocytopenia (ITP). Itaconate is a Krebs cycle-derived immunometabolite synthesized by myeloid cells to modulate cellular metabolism and inflammatory responses. This study aimed to evaluate the immunoregulatory effects of an itaconate derivative on macrophages in patients with ITP. Methods:. Peripheral blood-derived macrophages from patients with ITP and healthy controls were treated with 4-octyl itaconate (4-OI), a derivative of itaconate that can penetrate the cell membrane. Macrophage polarization, antigen-presenting functions, and phagocytic capability were measured via flow cytometry and enzyme-linked immunosorbent assay (ELISA). Macrophage glycolysis in patients with ITP and the metabolic regulatory effect of 4-OI were detected using a Seahorse XFe96 Analyzer. An active murine model of ITP was used to evaluate the therapeutic effects of 4-OI in vivo. Results:. 4-OI reduced the levels of CD80 and CD86 in M1 macrophages and suppressed the release of tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 pro-inflammatory cytokines, suggesting that 4-OI could hinder the polarization of macrophages toward an M1 phenotype. We found that 4-OI pretreated M1 macrophages reduced the proliferation of CD4+ T cells and promoted the differentiation of regulatory T cells. In addition, after 4-OI treatment, the phagocytic capacity of M1 macrophages toward antibody-coated platelets decreased significantly in patients with ITP. In addition, the glycolytic function of M1 macrophages was elevated in individuals with ITP compared to those in healthy controls. 4-OI treatment downregulated glycolysis in M1 macrophages. The glycolysis inhibitor 2-deoxy-d-glucose (2-DG) also inhibited the polarization of M1 macrophages and restored their functions. In vivo, 4-OI treatment significantly increased platelet counts in the active ITP murine model. Conclusions:. Itaconate derivative 4-OI inhibited M1 macrophage polarization and restored impaired functions through metabolic reprogramming. This study provides a novel therapeutic option for ITP.